Implementasi Manajemen Konflik Sebagai Upaya dalam Meningkatkan Produktivitas Kerja di Lembaga Pendidikan Islam - Nur Azizah, Ditha; Nurlaeli, Acep; Ma’shum, Sya’roni (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
Effective conflict management is an important factor in developing work productivity in an institution. Conflict that is not handled well can disrupt collaboration, reduce motivation, and affect the quality of teaching and relationships between individuals. Therefore, this research aims to explore the implementation of conflict management as an effort to develop work productivity in Islamic educational institutions. This research uses library research, based on literature search methods or using content analysis methods to identify patterns, themes, and results related to the implementation of conflict management, and then develop and analyze them to reach conclusions. The results of this research indicate that the implementation of effective conflict management has a positive impact on work productivity in an Islamic educational institution. In conclusion, this research emphasizes the importance of implementing effective conflict management in Islamic educational institutions. By managing conflict well, educational institutions can increase work productivity, teaching quality, and student participation, and create positive relationships between teaching staff, students, and related parties. The implications of the results of this research provide better knowledge about the role of conflict management in the context of Islamic education and provide a basis for the development of effective conflict management strategies in these educational institutions.